A circulating ventilation system to concentrate pollutants and reduce exhaust volumes: Case studies with experiments and numerical simulation for the rubber refining process. (March 2021) - Zeng, Lingjie; Liu, Guodong; Gao, Jun; Du, Bowen; Lv, Lipeng; Cao, Changsheng; Ye, Wei; Tong, Leqi; Wang, Yirui
Abstract: The emission standards of non-methane total hydrocarbon were tightened from 120 mg/m 3 to 10 mg/m 3 for Chinese industries in 2012. Despite the investment into environmental treatment, many factories have since been struggling to hit the emission reduction target. Emissions from various production processes have the characteristics of low concentration and intermittency, so the conventional ventilation systems relying on high flow rates to collect and exhaust the low-concentration pollutants often result in large scale, high economic and energy consequences, but poor performance. In this study, a novel circulating system was proposed to concentrate pollutants and reduce the exhaust air volume using a rubber refining process as an example. Firstly, a circulating ventilation model based on the mass balance was established to predict the variation of pollutant concentration within the system, and two control strategies (i.e. continuous or intermittent exhaust scheme) were developed to improve the pollutant capture efficiency of the system. Secondly, the emission intensity of pollutants in the rubber refining process was measured and further used as boundary conditions in the subsequent simulation. Thirdly, the CFD simulation was adopted to optimize the circulating air volume, return air jet angle, and exhaust air volume of the circulation system. Results showed that the optimized design of the circulation system with the continuous/intermittent exhaust scheme can achieve a 14.5/32.6 fold increase in the exhaust concentration of VOCs and a 75.8%/53.8% reduction in exhaust air volume. Highlights: A novel circulating ventilation system is proposed to concentrate pollutants and reduce exhaust volumes. Two exhaust schemes (i.e. continuous or intermittent) are developed and tested. The optimized design of the circulation system is determined by experiments-based CFD simulation.